A sequence-based 163plex microhaplotype assay for forensic DNA analysis - Tao, Ruiyang; Yang, Qi; Xia, Ruocheng; Zhang, Xiaochun; Chen, Anqi; Li, Chengtao; Zhang, Suhua (Frontiers in Genetics, 2022)
Novel genetic marker microhaplotype has led to an upsurge in forensic genetic research. This study established a 163 microhaplotype (MH) multiplex assay based on next-generation sequencing (NGS) and evaluated the assay’s performance and applicability. Our results showed that the 163 MH assay was accurate, repeatable and reliable, and could distinguish between African, European-American, Southern Asia and Eastern Asia populations. Among the 163 MH makers, 48 MHs with Ae > 3.0 in China Eastern Han were selected and confirmed to be highly polymorphic, with a combined power of discrimination of 1-8.26×10-44 and the combined power of exclusion in duos and trios of 1-1.26×10-8 and 1-8.27×10-16, respectively. Moreover, the mixture study demonstrated the realizability of the MHs in deconvoluting mixtures with different proportions of two to five-person. In conclusion, our findings support the use of this MH assay for ancestry inference, human identification, paternity testing and mixture deconvolution in forensic research.